Combined Otoplasty - Osvaldo Ribeiro Saldanha; Osvaldo Ribeiro Saldanha; Cristianna Bonneto Saldanha; Paulo Rodamilans Sanjuan; Sabina Aparecida Alvarez de Paiva; Bernardo Fernandes de Souza Fontes; Flávio Francescheli; Naby Gebrim; Francisco Felipe Góis de Oliveira (Revista Brasileira de Cirurgia Plástica, 2018)
Introduction: Protruding ear is the most common congenital deformity of the head and neck, with an autosomal dominant inheritance and no predilection for sex. Protruding ear or prominent ear occurs when there is concha excess or hypertrophy, erasure of the antihelix, a scapho-conchal angle greater than 90º, or a combination of these factors, occurring uni- or bilaterally. The objective is to present a conservative approach to correct protruding ear, with a combination of techniques. Methods: The otoplasty surgical technique involved an anterior approach for resection of the auricular concha, which was associated with weakening of the antihelix, and partial incisions of the cartilage were performed through anterior access and of Mustardé sutures, through posterior access for better definition of the antihelix without fixation of the concha to the mastoid. Two hundred patients with a mean age of 17 years underwent operations between January 1987 and January 2015, 60% of whom were female. Results: Of the 200 patients, only 24 patients needed discrete surgical revisions. Conclusion: The surgical procedure is simple, easily reproducible, provides good results, and is associated with a high degree of satisfaction and a low rate of complications/morbidities.